1986
DOI: 10.1177/106002808602001017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Computerized Reminder System in the Enhancement of Patient Medication Refill Compliance

Abstract: This study evaluated the use of a computerized patient profile combined with a reminder system to increase refill compliance of patients on cardiovascular medications. There were 311 patients randomly assigned into one of three groups. Patients in group 1 were monitored for refill compliance only. Group 2 patients received a postcard reminder; group 3 patients received a telephone call reminder. Refill compliance was monitored via the computerized patient profile system for a period of three months. Data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A review of the literature showed that the introduction of adherence aids and refill or follow‐up reminders increased adherence by 6–25% 47 . In addition, adherence as determined by prescription refills was significantly increased in patients receiving a computer‐generated postcard or telephone reminder 60 …”
Section: Strategies To Optimize Adherence In Ucmentioning
confidence: 99%
“…A review of the literature showed that the introduction of adherence aids and refill or follow‐up reminders increased adherence by 6–25% 47 . In addition, adherence as determined by prescription refills was significantly increased in patients receiving a computer‐generated postcard or telephone reminder 60 …”
Section: Strategies To Optimize Adherence In Ucmentioning
confidence: 99%
“…Another type of reminder is a refill reminder which is generated at the pharmacy level. S i n s and Wenzloff (68) investigated the use of postcard refill reminders and telephone-call refill reminders. These researchers found that both types of reminders increased refill compliance, but there were no significant differences in compliance between the two types.…”
Section: Behavioural Strategiesmentioning
confidence: 99%
“…An inner-city university health center utilized a computerized reminder system to increase refill behavior among 311 patients randomly assigned into three groups: control, postcard reminder, and telephone call reminder. 14 The study found a significant difference in the mean refill rate between the control and the two intervention groups; however, there was no significant difference between the postcard reminder and telephone call reminder intervention groups. Albright and colleagues 15 conducted a qualitative study among African American health plan members of Kaiser Permanente Colorado to evaluate the use of a linguistically congruent voice in interactive voice response calls as a strategy to improve call completion rates.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the outreach call did not include any messaging about the benefits of taking the medication, such as LDL‐C or BP reduction and reduced risk of a heart attack or stroke. An inner‐city university health center utilized a computerized reminder system to increase refill behavior among 311 patients randomly assigned into three groups: control, postcard reminder, and telephone call reminder . The study found a significant difference in the mean refill rate between the control and the two intervention groups; however, there was no significant difference between the postcard reminder and telephone call reminder intervention groups.…”
Section: Discussionmentioning
confidence: 99%